Continuous One‐Step Synthesis of Porous M‐XF6‐Based Metal‐Organic and Hydrogen‐Bonded Frameworks. Issue 28 (25th April 2017) - Guillerm, Vincent; Garzón‐Tovar, Luis; Yazdi, Amirali; Imaz, Inhar; Juanhuix, Jordi; Maspoch, Daniel
Abstract: Metal‐organic frameworks (MOFs) built up from connecting M‐XF6 pillars through N‐donor ligands are among the most attractive adsorbents and separating agents for CO2 and hydrocarbons today. The continuous, one‐step spray‐drying synthesis of several members of this isoreticular MOF family varying the anionic pillar (XF6 =[SiF6 ] 2− and [TiF6 ] 2− ), the N‐donor organic ligand (pyrazine and 4, 4′‐bipyridine) and the metal ion (M=Co, Cu and Zn) is demonstrated here. This synthetic method allows them to be obtained in the form of spherical superstructures assembled from nanosized crystals. As confirmed by CO2 and N2 sorption studies, most of the M‐XF6 ‐based MOFs synthesised through spray‐drying can be considered "ready‐to‐use" sorbents as they do not need additional purification and time consuming solvent exchange steps to show comparable porosity and sorption properties with the bulk/single‐crystal analogues. Stability tests of nanosized M‐SiF6 ‐based MOFs confirm their low stability in most solvents, including water and DMF, highlighting the importance of protecting them once synthesised. Finally, for the first time it was shown that the spray‐drying method can also be used to assemble hydrogen‐bonded open networks, as evidenced by the synthesis ofMPM‐1‐TIFSIX . Abstract : Dry run : Industry‐derived spray drying technology has been successfully applied to synthesise one of the most promising subclass of metal‐organic frameworks, M‐XF6 based MOFs, which exhibit exceptional CO2 sorption properties.